The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s10637-017-0441-4
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1b trial of proteasome inhibitor carfilzomib with irinotecan in lung cancer and other irinotecan-sensitive malignancies that have progressed on prior therapy (Onyx IST reference number: CAR-IST-553)

Abstract: Summary Introduction Proteasome inhibition is an established therapy for many malignancies. Carfilzomib, a novel proteasome inhibitor, was combined with irinotecan to provide a synergistic approach in relapsed, irinotecan-sensitive cancers. Materials and Methods Patients with relapsed irinotecan-sensitive cancers received carfilzomib (Day 1, 2, 8, 9, 15, and 16) at three dose levels (20/27 mg/m2, 20/36 mg/m2 and 20/45 mg/m2/day) in combination with irinotecan (Days 1, 8 and 15) at 125 mg/m2/day. Key eligibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Two of the five cell lines acquired increased sensitivity to IPI compared with their parental counterparts while developing resistance to cisplatin. This result may be consistent with the results of several clinical trials that have shown that proteasome inhibitors are clinically effective in a small but distinct subset of lung cancers, especially platinumpretreated patients with lung cancers [28][29][30][31].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Two of the five cell lines acquired increased sensitivity to IPI compared with their parental counterparts while developing resistance to cisplatin. This result may be consistent with the results of several clinical trials that have shown that proteasome inhibitors are clinically effective in a small but distinct subset of lung cancers, especially platinumpretreated patients with lung cancers [28][29][30][31].…”
Section: Discussionsupporting
confidence: 88%
“…Proteasome inhibitors and IPIs have prolonged survival of patients with relapsed or refractory multiple myeloma [25][26][27]. In addition, several clinical trials have shown that PIs are clinically effective in a small but distinct subset of lung cancers [28][29][30][31]. Drilon et al reported that 1 out of 16 patients with KRAS G12D-mutant lung adenocarcinoma, who was pretreated with carboplatin and pemetrexed and subsequent gemcitabine, showed remarkable tumor shrinkage after bortezomib treatment in a phase 2 trial [28].…”
Section: Introductionmentioning
confidence: 99%
“…For example, bortezomib showed modest singleagent activity in patients with relapsed or refractory advanced non-small cell lung cancer (36). Objective clinical response for carfilzomib combined with irinotecan had 19% partial response and 6% stable disease in small cell lung cancer in a phase I clinical study (37). However, there is a strong need to improve the antitumor activity of proteasome inhibitors in order to advance them in the clinic for solid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Carfilzomib is a selective proteasome inhibitor being investigated in a number of malignancies including SCLC. The safety of carfilzomib in combination with irinotecan was established in a phase 1 trial [81]. This combination was further evaluated in a phase 2 trial of 62 relapsed SCLC patients.…”
Section: Epigenetic Targetingmentioning
confidence: 99%